THE INFLUENCE OF COMPUTATIONAL THINKING SHEET FOR KIDS (CTSK) MEDIA ON COGNITIVE DEVELOPMENT ASPECTS OF CHILDREN AGED 5-6 YEARS - Sindy Anugerah; Regina Christine Takumansang; Anita Roslina Simanjuntak; Kristin Anggraini (Magister Scientiae, 2024)
Computational Thinking (CT) or computational thinking is a cognitive or thinking process that involves logistical reasoning. CT needs to be taught to children from an early age because it can help children develop critical thinking skills, creativity and problem-solving abilities which are developed through aspects of cognitive development using Computational Thinking Sheet For Kids (CTSK) media. The research was carried out at Indriyasana VII Kindergarten Surabaya with the aim of finding out the effect of using CTSK media on the cognitive development of children aged 5-6 years. CTSK is a computing-based learning media specifically designed for pre-school children. This research uses quantitative research methods with a pre-experimental design. The design used is one group pretest-posttest design. The sampling technique used in this research is nonprobability sampling. The nonprobability sampling technique used in this research was saturated sampling. This research consists of 2 variables, variable x, namely CTSK and variable Y, namely aspects of cognitive development. The results of data analysis in this study used the IBM SPSS Statistics 26 application. Based on the research that has been carried out, the results of normality test data analysis using the Kolmogrov Smirnov test, it can be seen that the result is 0.11, meaning the data in this study is normally distributed. Meanwhile, the results of data analysis used the Paired Sample T-test with a sig (2 tailed) value of 0.000, which means Ha was accepted and H0 was rejected. So it can be concluded that the results of this study show that the use of CTSK has a significant influence on the cognitive development of children aged 5-6 years. Thus, the use of Computational Thinking Sheet For Kids (CTSK) media can be an effective alternative in facilitating the cognitive development of children aged 5-6 years at Kindergarten Indriyasana VII Surabaya. Implementation of CTSK can help children develop computational thinking skills, solve problems and improve other cognitive activities